(untitled) - Pascarelli, Emil F. (Hoboken, N.J., 2004)
One of the world’s leading authorities on repetitive strain injury tells you how to prevent, treat, and recover from RSI. Living with repetitive strain injury (RSI) can be painful, exasperating, and devastating. If you’ve given up hope that there is any help for your symptoms, if you’ve tried medications, wrist splints, neck braces, and exercises–and have had only temporary relief–this book is for you. Dr. Emil Pascarelli, one of the world’s leading authorities on RSI, offers a comprehensive, prescriptive, practical, and long-awaited sequel to his bestselling Repetitive Strain Injury.
Keywords: Overuse injuries,Carpal tunnel syndrome,Lạm dụng chấn thương